Isometric exercises with elements postisometric relaxation to eliminate the knee joint contracture after arthroscopic plastics of anterior cruciate ligament - O.V. Pylypenko; A.A. Zakharov; K.A. Sribniy; A.K. Nikanorov (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : to determine the efficiency of isometric exercises and post isometric relaxation of character for removal and prevention of contractures and recovery of motor function after arthroscopic reconstruction of the anterior cruciate ligament in the late postoperative period. Material: The study involved 22 patients aged less than 40 years. Results: The results showed that the level of pain decreased equally in patients of main and control group from 3 to 0 points, the performance difference in the amplitude of the bending of the knee joint during the goniometry in the treatment group was 70 in the control group - 30 and the extension 10 - fixed, reaching 5 hyperextension and not changed in the control group. Conclusions: The use of isometric exercises and post isometric relaxation prevent postoperative contracture of the knee joint. Methods of their application are recommended for use in the comprehensive rehabilitation of patients after arthroscopic plastics anterior cruciate ligament.